Revelando a diversidade taxonômica de Pseudisobrachium Kieffer, 1904 (Hymenoptera: Chrysidoidea: Bethylidae) na Região Amazônica Brasileira - Gomes, Leonardo Alho (Entomologia, 2025)
The genus Pseudisobrachium Kieffer, 1904 (Hymenoptera: Bethylidae: Pristocerinae) is globally distributed, with species present in all major biogeographic regions except Antarctica, and currently includes approximately 194 formally recognized species. Of these, 61 species of Pseudisobrachium have been described from Brazil. However, morphological studies characterizing the genus have been focused on the Atlantic Forest biome. Despite this broad distribution and frequent representation in museum collections, Pseudisobrachium remains one of the most taxonomically neglected genera within Bethylidae. This taxonomic gap is particularly evident in the Brazilian Amazon, where only four species have been recorded, all from limited localities in the states of Amazonas and Pará. In this context, the Invertebrate Collection of the Instituto Nacional de Pesquisas da Amazônia (INPA) is one of the most significant insect collections in Brazil, encompassing a vast diversity of species. It is particularly notable for its Hymenoptera collection, considered one of the most important in the country. The present study aims to reassess the taxonomy and distribution of Pseudisobrachium in the Brazilian Amazon, providing the revision of all known Amazonian species, describing new species, providing an updated identification key, and refining the geographic distribution. During this work, we recognized 40 species for the Brazilian Amazon, seven of which were previously described: P. brasiliense Kieffer, 1910; P. crassicornis (Westwood, 1874); P. inchoatum Kieffer, 1910; P. rufopictum (Kieffer, 1910), previously registered. In addition to P. angulatum Evans, 1964 and P. pauxillum Evans, 1969, recorded for the first time in Brazil, and P. corvinum Evans, 1969 in the Brazilian Amazon. So, the Brazilian fauna of Pseudisobrachium now is represented by 96 species. These findings underscore the remarkable, yet previously underestimated, diversity of Pseudisobrachium in the Amazon biome.
Keywords: Pseudisobrachium; Bethylidae; Diversidade amazônica; Vespas-achatadas